KOMPOSISI ASAM LEMAK NEUTRAL LIPID OF MUSCLE DAN INTERMUSCULAR ADIPOSE TISSUE LIPID ANTARA SAPI WEANERS DAN MATURES - Husain, Muh Hamsun (AgriSains, 2016)
The objective of this research is to characterize fatty acid compositions of neutral lipids of muscle (NLM) and inter-muscular adipose tissue (IAT) lipids of weaners compared to the matures. The outcomes of this research will be basic information to change the fatty acid composition in producing healthy meat according to the consumer prespectives.Sixteen cattle, consisted of eight Donggala and Bali cattle, which each breed consisted of four weaners and matures respectively were slaughtered, then muscle of Longisimus Dorsi and intermuscular adipose tissue samples were taken for fatty acid composition analyses by Gas Chromatography.This research found eleven saturated fatty acids and eleven unsaturated fatty acids in NLM and IAD. The saturated fatty acid are Capric acid (C10:0), Lauric acid (C12:0), Tridecylic acid (C13:0), Myristic acid (C14:0), Pentadecylic acid (C15:0), Palmitic acid (C16:0), Margaric acid (C17:0), Stearic acid (C18:0), Arachidic acid (C20:0), Behenic acid (C22:0), dan Lignoceric acid (C24:0). The eleven unsaturated fatty acids found consisted of 5 MUFAs and 6 PUFAs. The MUFAs are Miristoleic acid (C14:1), Palmitoleic acid (C16:1), Oleic acid (C18:1), Gadoleic acid (C20:1), dan Nervonic acid (C24:1). The PUFAs are Linoleic acid (LA)(C18:2), α-Linolenic acid (ALA) (C18:3), Arachidonic acid (AA)(C20:4), Eicosapentaenoic acid (EPA)(C20:5), Erucic acid (C22:1) dan Docosahexaenoic acid (DHA) (C22:6).Oleic acid was found to be the most abundant, with proportion of more than 60%, of 22 fatty acids detected, followed by Palmitic acid around 25%. Myristic acid, Pentadecylic acid, Margaric acid dan Palmitoleic acid had concentration ranged between 1 to 3%, whiles the others had concentration of less than 1% respectivelly. Oleic concentration of NLM in weaners (65,748 ± 1,539) was found to be significant higher (P<0.05) than that in matures (60,635 ± 1,440). For other unsaturated fatty acids, Miristoleic acid (C14:1) was found to be lower (P<0.05) in NLM of weaners (0,095 ± 0,024) compared to that of matures (0,186 ± 0,023). This research also found the difference in Capric acid concentration of NLM between weaners and matures, which weaner (0,024 ± 0,006) was highly significant lower (P<0.01) than mature (0,063 ± 0,006). This research did not find any difference in both saturated-and unsaturated fatty acid concentrations between weaners and matures in IAT lipids.Keywords: fatty acid composition, neutral lipids of muscle, inter-muscular adipose tissue, weaners, matures, donggala cattle.